Intraoral management of displaced root into submandibular space under local anaesthesia –A case report and review of literature - Satnam Singh Jolly; Vidya Rattan; Sachin Kumar Rai (Saudi Dental Journal)
Accidental displacement of an impacted third molar, either a root fragment, crown, or the entire tooth, is a rare complication that occurs during exodontia. The most common sites of dislodgment of an impacted mandibular third molar fragment are the sublingual, submandibular, and pterygomandibular spaces. Removal of a displaced root tip from these spaces may be complex due to poor visualization and limited access. A thorough evaluation of all significant risk factors must be performed in advance to prevent complications. This paper reports the case of a patient who presented with a mandibular third molar root that was displaced into submandibular space. The case was managed intraorally under local anaesthesia and review of the literature. Keywords: Third molar, Root displacement, Intraoral, Local anaesthesia, Submandibular space